Metode Profile Matching Dalam Sistem Pendukung Keputusan Pemilihan Pegawai Terbaik - Imaduddin , Encep Fahmi; Sutinah , Entin; Agustina , Nani (Journal of Students‘ Research in Computer Science, 2023)
Tri Jaya Mart has implemented a best employee selection system to motivate its employees to have a better career path. However, the selection of employees currently only looks at one employee with the highest attendance rate every month and if there is the same then it is chosen subjectively. Selection in this way, researchers feel less effective because it only uses one criterion by not paying attention to other supporting criteria and often more than one best employee candidate is obtained. As well as conflicts between employees due to injustice during promotion. The purpose of this research is to find out the best employee selection process that is currently running where currently out of five employees who work at Tri Jaya Mart, in the process of selecting the best employee, implementing the profile matching method in making a decision so as to provide alternative problem solving in choosing the best employee to be promoted to store manager. In this study using three criteria, namely aspects of work attitude, personality aspects and intelligence aspects. From several steps that have been applied using the profile matching method, the results obtained are the right decision and as expected for stakeholders in choosing the best employee in the order of employee two, employee four, employee one, employee three and employee five.